Learning Fun English Using Total Physical Response Method - Zulia Karini (Universitas Muhammadiyah Mataram, 2018)
One of the difficult parts of learning the target language for English language learners is the acquisition of vocabulary. Most learners find that English is a hard subject to be studied. However, they can enjoy learning English when it is taught in a fun way. Using games for teaching vocabulary has been very popular for several decades. Different studies revealed that games are beneficial in vocabulary learning because they enhance students’ ability to memorize words, encourage student’s interaction, improve their communicative skills and enhance students’ motivation. Games also can help the teachers to create contexts in which the language is useful and meaningful. Watching a movie is also a great way to learn English. Learners can improve their vocabulary while watching a film. Total Physical Response method can also be applied when teaching English for children. This method makes language skills more quickly understood and understood by children the use of functional English like